Ответы и объяснения

2012-12-05T23:32:58+04:00

Если правильно поняла условие, то

15 7/6 + (28 1/2 - 13 5/8) = 

15*6+7          28*2+1         13*8+5            97        57    109        97*4       57*12-109*4)

--------- + (  ---------  -  ------------) =  ------- + (---- -  -----) = -------- + (---------------

6                       2                 8                 6           2        8           24                   24

 

 

 

   388 + 248        636              12

= ------------- = --------- = 26 ---- = 26,5

 

         24              24              24

 

 

 

 

 

 

 

  • Участник Знаний
2012-12-05T23:48:07+04:00

                                          решение:

 вот так верно будет

 

 

15 7/6 + (28 1/2 - 13 5/8) = 26,5

15*6+7          28*2+1         13*8+5            97        57    109        97*4       57*12-109*4)

______ + (  ______  -  ___________) =  _____ + (___- ____) = ______ + (__________

6                       2                 8                 6           2      8           24                   24

 

 

 

   388 + 248        636              12

=_________ = ______ = 26 ---- = 26,5

 

         24              24              24